Implementation Inquiry Model with Examples and Non Examples to Enhance The Mathematical Conceptual Understanding of Primary School Students - Ananda, Tegar; Prabawanto, S (International Conference on Elementary Education, 2020)
The ability to understand concept is one of the abilities which is students must possess in mathematics learning. Inquiry model allows students to be actively involved in constructing the concept. Inquiry makes students become a researcher or scientist, but in the context of learning, students are still guided by the teacher. The research aims to analyze the effect of inquiry model with examples and non-examples on primary school students’ mathematical conceptual understanding. The method used in the research was a library research. The result of the research are that the inquiry model with examples and nonexamples can enhance students’ mathematical conceptual understanding and the steps of inquiry model with examples and non- examples is relevant with the indicators of students’ mathematical conceptual understanding